SISTEM ENKRIPSI FILE DENGAN ID-CARD MENGGUNAKAN LARAVEL - Diva Ramadhan; Muhammad Imam Gunawan (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2025)
The security of digital data has become crucial in today's era of information exchange. Many data breaches occur due to weak file protection in web-based systems. This research aims to design and develop a web-based file encryption system using the Advanced Encryption Standard (AES) algorithm, where file access is restricted only to users who possess a valid ID Card or QR Code as an authentication key. The software development approach adopted in this development is the Waterfall methodology, which follows a sequential process consisting of requirement analysis, system design, implementation, and testing phases. The software was built using the Laravel framework with key features such as automatic file encryption upon upload, folder management, and additional authentication through ID Card or QR Code scanning. Administrator has full access to manage users while regular users can only upload and manage their private files. The implementation result show that files were successfully encrypted and can only be accessed using a valid ID Card. The AES encryption process effectively secures file confidentiality, while the use of an ID Card enhances access security to the uploaded files. Therefore, this software can fulfills the research objective of improving file security in web-based systems.